Chapter Famiglie signorili delle valli di Non e di Sole - Bettotti, Marco (Reti Medievali E-Book, 2023)
With reference to the 14th and 15th centuries, the essay analyses the specific characteristics of the rural lordships of the Val di Non and Val di Sole, territories of the Episcopal principality of Trento, particularly subject to Tyrolean influence.